Field notes contributed by Babs Padelford and Loren Padelford, fall 1993 - Padelford, Babset al; Padelford, Lorenet al (1993)
Fall report of birds found in western Iowa contributed by Babs Padelford and Loren Padelford. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1993. Plustek - flatbed